2024
DOI: 10.1021/acsptsci.4c00163
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Polyphenolic Imidazo[4,5-c]quinoline Derivatives to Modulate Toll Like Receptor-7 Agonistic Activity and Adjuvanticity

Kushvinder Kumar,
Binita Sihag,
Madhuri T. Patil
et al.

Abstract: TLR-7/8 agonists are a well-known class of vaccine adjuvants, with a leading example now included in Covaxin, a licensed human COVID-19 vaccine. This thereby provides the opportunity to develop newer, more potent adjuvants based on structure−function studies of these classes of compounds. Imidazoquinoline-based TLR7/8 agonists are the most potent, but when used as a vaccine adjuvant side effects can arise due to diffusion from the injection site into a systemic circulation. In this work, we sought to address t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…We recently evaluated the adjuvant potential of m -IMDG ( 12 ) for protein-based vaccines . In the present study, the mice were immunized with Sp and HBs along with m -IMDG ( 12 ) or p -IMDG ( 13 ) or p -IMDP ( 14 ) alone or in combination with alum (Figures and ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We recently evaluated the adjuvant potential of m -IMDG ( 12 ) for protein-based vaccines . In the present study, the mice were immunized with Sp and HBs along with m -IMDG ( 12 ) or p -IMDG ( 13 ) or p -IMDP ( 14 ) alone or in combination with alum (Figures and ).…”
mentioning
confidence: 99%
“…The SAR investigation on IMDQ revealed that N -acylation of aminomethyl functionality reduced TLR7 and TLR8 agonist activity. Considering that vic -phenolic functionality helps in the adsorption of TLR7/8 agonists to alum, we designed a 7,8-dihydroxyimidazoquinoline derivative (dh- p -AM-BBIQ, 21 ) where the aluminum-coordinating vic -diphenolic functionality was introduced in the quinoline ring, leaving free the aminomethyl group on the N 1-benzyl group to interact with TLR7/8. The synthesis of the desired target compound 21 was achieved from 4-chloro-6,7-dimethoxy-3-nitroquinoline ( 15 ) (Scheme ) following a similar synthetic protocol as described in Scheme , except that the demethylation of intermediate 20 was carried out using BBr 3 in anhydrous dichloromethane at −78 °C (Scheme ).…”
mentioning
confidence: 99%
See 1 more Smart Citation